UI/UX Prototype Design of Employee Presence Application Using Design Thinking - Sri Widagdo, Adika; Sapurtro , Fachruddin Edi Nugroho; Qodri, Krisna Nuresa; Ronaldo, Rizal Adimas (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2025)
Employee Presence management is a crucial aspect of organizational productivity. However, manual Presence systems often result in inefficiencies, requiring alternative technological solutions. This study aims to design a UI/UX prototype for a mobile-based Presence application at Universitas Muhammadiyah Klaten using the Design Thinking approach. The research follows five stages: Empathize, Define, Ideate, Prototype, and Test. Data collection involved surveys and interviews with 62 respondents, including lecturers, staff, and education personnel. The prototype was evaluated using the System Usability Scale (SUS), resulting in a usability score of 76.6% in the "Good" category. The findings indicate that the proposed design effectively addresses the limitations of manual presence systems, enhancing user experience and efficiency. Future improvements include additional features such as a "forgot password" option, different presence button and broader usability testing. This study suggests that a well-designed presence application can streamline presence recording and improve operational effectiveness.